2017
DOI: 10.1182/blood-2016-08-736587
|View full text |Cite
|
Sign up to set email alerts
|

Distinct roles for TET family proteins in regulating human erythropoiesis

Abstract: The ten-eleven translocation (TET) family of proteins plays important roles in a wide range of biological processes by oxidizing 5-methylcytosine (5mC) to 5-hydroxy-methylcytosine. However, their function in erythropoiesis has remained unclear. We show here that TET2 and TET3 but not TET1 are expressed in human erythroid cells, and we explore the role of these proteins in erythropoiesis. Knockdown experiments revealed that TET2 and TET3 have different functions. Suppression of TET3 expression in human CD34 cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
83
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(95 citation statements)
references
References 48 publications
4
83
0
Order By: Relevance
“…This is the case for Tet2 (and to a lesser degree Tet3), which is consistently reported in murine models [39,40,43,[45][46][47]49] and human cells [37,38,42,[50][51][52]. Of note, the role of Tet2 in mast cell differentiation described above [40] is partially independent of 5hmC, as rescuing mast cell developmental changes upon Tet2 knockout was only possible by the re-expression of Tet2 independently of its catalytic activity, which assumes that Tet2 possibly interacts with other complexes (something similar has been shown between TET1 and the SIN3A co-repressor complex [53]).…”
Section: Specific 5-hydroxymethylcytosine Enrichment Identifies Bloodmentioning
confidence: 52%
“…This is the case for Tet2 (and to a lesser degree Tet3), which is consistently reported in murine models [39,40,43,[45][46][47]49] and human cells [37,38,42,[50][51][52]. Of note, the role of Tet2 in mast cell differentiation described above [40] is partially independent of 5hmC, as rescuing mast cell developmental changes upon Tet2 knockout was only possible by the re-expression of Tet2 independently of its catalytic activity, which assumes that Tet2 possibly interacts with other complexes (something similar has been shown between TET1 and the SIN3A co-repressor complex [53]).…”
Section: Specific 5-hydroxymethylcytosine Enrichment Identifies Bloodmentioning
confidence: 52%
“…Pronier et al [8] demonstrated that the TET2 silencing increased granulomonocytic differentiation in detriment of erythroid differentiation in normal CD34 + cells. Yan et al [9], similarly demonstrated that TET2 inhibition led to MDS-like dyserythropoiesis. Of note, TET2 deletion leads to erythroid dysplasia and anemia in zebrafish model [14], suggesting a conserved function for TET2 in erythrocytes production.…”
Section: Discussionmentioning
confidence: 80%
“…Despite extensive studies, the specific contribution of TET2 in disease phenotype of myeloid neoplasms is not fully elucidated. Recent findings have brought attention to the role of TET2 in normal and malignant erythropoiesis [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The resulting five populations/stages are henceforth colorcoded as follows: progenitors (mostly CFU-E) (Hu et al, 2013;Li et al, 2014a;Yan et al, 2017), yellow; ProE/EBaso, blue; LBaso day7, light pink; LBaso day14, dark pink; Poly, dark blue, and Ortho, orange ( Figure 1A-B).…”
Section: Establishing Stage-specific Proteomes Of Human Erythropoiesismentioning
confidence: 99%